Laboratory simulations of supernova shockwave propagation - Hansen, J; Edwards, M; Froula, D; Gregori, G; Edens, A; Ditmire, T (2005)
Supernovae launch spherical shocks into the circumstellar medium (CSM). These shocks have high Mach numbers and may be radiative. We have created similar shocks in the laboratory by focusing laser pulses onto the tip of a solid pin surrounded by ambient gas; ablated material from the pin rapidly expands and launches a shock through the surrounding gas. Laser pulses were typically 5 ns in duration with ablative energies ranging from 1-150 J. Shocks in ambient gas pressures of similar to 1 kPa were observed at spatial scales of up to 5 cm using optical cameras with schlieren. Emission spectroscopy data were obtained to infer electron temperatures (< 10 eV).In this experiment we have observed a new phenomena; at the edge of the radiatively heated gas ahead of the shock, a second shock forms. The two expanding shocks are simultaneously visible for a time, until the original shock stalls from running into the heated gas. The second shock remains visible and continues to expand. A minimum condition for the formation of the second shock is that the original shock is super-critical, i.e., the temperature distribution ahead of the original shock has an inflexion point. In a non-radiative control experiment the second shock does not form. We hypothesize that a second shock could form in the astrophysical case, possibly in radiative supernova remnants such as SN1993J, or in shock-CSM interaction.